FACTORS AFFECTING USER BEHAVIOR OF TECHNOLOGY APPLICATION OF MANAGEMENT INFORMATION SYSTEM - Lisa Rosiana; Musa Hubeis; Eko Ruddy Cahyadi (School of Business, IPB University (SB-IPB), 2020)
This research aimed to determine the factors influencing the behavior of management information system users at the National Accreditation Committee. The theory used was based on the Technology Acceptance Model (TAM) theory extension, and the analytical method used was the Structural Equation Model (SEM). The factors were according to Davis's modified theory, where external factors were the quality of internet connection and leadership support. Internal factors included perceived ease of use and perceived usefulness, attitudes toward using, behavioral intention to use, and actual system use. This research was conducted on 128 respondents representing the Conformity Assessment Bodies (CABs). This research showed that leadership support had a significant effect on perceived ease of use and perceived usefulness. Meanwhile, the quality of the internet connection only affected the perceived usefulness. Leadership support, quality of internet connection, perceived ease of use, perceived usefulness, and attitudes toward using were factors that affected user behavior intention to use. This research's managerial implication is to strengthen the server and increase the leadership's motivation towards the CAB employees by socializing accreditation applications. Keywords: behavioral intention to use, information system, leadership support, quality of internet connection, TAM